Designing creative organizations : tools, processes and practice - Hawryszkiewycz, I. T. (Emerald Group Publishing Limited, 2016)
'Designing Creative Organizations' is one of the first books to cover ways to organize creativity, innovation and business model development in a way that provides a seamless transition from an idea generated through team brainstorming to a business solution. It provides systematic ways to design new business models, and how to choose technologies to support them. By defining agility as continuous business model innovation, the book describes how organizations can become agile in an increasingly complex and disruptive world. Drawing on current developments, the book examines both large and medium-sized organizations successfully creating a design-centric culture to encourage innovation in their products and in the ways that they engage with clients. Design-centric culture is seen here as one where people throughout the business ask the question: 'how do I design my business to make things work better', rather than 'how do I use the existing system to do something'. This book will be of value to all those who are designing business systems in volatile environments and for students and researchers of innovation, design thinking, business model design and product development.